Certain aspects for intensification of tropical storms over Indian Ocean area - BANSAL, R. K.; DATTA, R. K. (MAUSAM, 1972)
Palmen (1956) gave three climatological and geographical conditions as pre-requisites for the formation of tropical storms. One of these being that the region of formation of storm should be over sufficiently large sea or ocean area with temperature of the sea surface so high that airmass shifted from the lowest layers of the atmosphere and expanded adiabatically with condensation remains considerably warmer than the surrounding undisturbed atmosphere at least between 500 and 200 mb. The temperature differences for island stations of Port Blair and Minicoy and the coastal stations were studied to test the above hypothesis for Indian area. In general it is found that Palmen's hypothesis holds good over the Bay of Bengal as well as the Arabian Sea.